Ypt/Rab GTPases and their TRAPP GEFs at the Golgi. Issue 17 (21st August 2019) - Lipatova, Zhanna; Segev, Nava
Abstract : The conserved Ypt/Rab GTPases regulate the different steps of all intracellular trafficking pathways. Ypt/Rabs are activated by their specific nucleotide exchangers termed GEFs, and when GTP bound, they recruit their downstream effectors, which mediate vesicular transport substeps. In the yeast exocytic pathway, Ypt1 and Ypt31/32 regulate traffic through the Golgi and the conserved modular TRAPP complex acts a GEF for both Ypt1 and Ypt31/32. However, the precise localization and function of these Ypts have been under debate, as is the identity of their corresponding GEFs. We have established that Ypt1 and Ypt31 reside on the two sides of the Golgi, early and late, respectively, and regulate Golgi cisternal progression. We and others have shown that whereas a single TRAPP complex, TRAPP II, activates Ypt31, three TRAPP complexes can activate Ypt1: TRAPPs I, III, and IV. We propose that TRAPP I and II activate Ypt1 and Ypt31, respectively, at the Golgi, whereas TRAPP III and IV activate Ypt1 in autophagy. Resolving these issues is important because both Rabs and TRAPPs are implicated in multiple human diseases, ranging from cancer to neurodegenerative diseases. Abstract :